Years after the cure: a rare case of delayed onset of oesophageal stricture post-radiotherapy for lung cancer - Sasa Shakya; Abhishek Tamrakar; Gurjit Singh (Clinical Medicine)
Introduction: Oesophageal stricture is a known long-term complication of radiotherapy, particularly in patients treated for head, neck and thoracic cancers.1 The risk of developing this condition can depend on several factors, including the radiation dose, the specific treatment approach and the location of the tumor.1 Typically, oesophageal strictures develop between 3 and 8 months after the completion of radiation therapy, with most cases occurring around the 6-month mark. However, while these early-onset strictures are more common, it is rare, although not impossible, for strictures to develop many years after treatment.3 In this case, we report a rare instance of an oesophageal stricture that occurred 7 years after radiotherapy for lung cancer. Method and materials: This is a retrospective case review. Relevant clinical information, including the patient’s background, radiotherapy details, onset of symptoms, diagnostic findings (from endoscopy and imaging) and treatment strategies, was gathered from electronic and paper medical records. The case’s management and outcome were carefully documented. A literature review was undertaken to explore the rarity of this condition. Case discussion: We present the case of a 69-year-old man who developed a cervical oesophageal stricture 7 years following radiotherapy for squamous cell carcinoma of the right upper lobe of the lung.In August 2016, the patient was diagnosed with squamous cell carcinoma of the right upper lobe of the lung (T4N0Mx). His treatment regimen included multimodal therapy, beginning with down-staging chemotherapy consisting of cisplatin and gemcitabine in September 2016. This was followed by radical radiotherapy, with a total dose of 54 Gy administered in 36 fractions over a period from 9 January 2017 to 20 January 2017.In May 2024, the patient presented with a recurrent issue of food sticking in his throat. This was associated with food regurgitation and dysphagia, mainly associated with solid foods.To investigate the patient's symptoms, a gastroscopy was performed, revealing a benign stricture located 24 cm from the mouth, with the gastroscope unable to pass through the narrowed segment. Histological examination of biopsy samples confirmed active oesophagitis. A barium swallow and meal showed a short segment of smooth narrowing in the mid-oesophagus, measuring up to 3 cm in length, with a narrowest diameter of 5 mm (Figs 1 and 2). Despite the narrowing, the flow of contrast material through the stricture was satisfactory, with the overall impression being that of a benign oesophageal stricture. Conclusion: This case highlights the importance of long-term monitoring for patients who have received thoracic radiotherapy, because they are at risk for developing oesophageal strictures and other complications.Early recognition of these complications through appropriate investigations can help guide treatment decisions, improve quality of life and ensure optimal outcomes for patients.Regular follow-up care is essential for detecting any late complications of treatment, particularly when the patient presents with symptoms suggestive of oesophageal involvement.All patients should be counselled regarding long-term risk of oesophageal stricture risk post radiotherapy.